The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.4314/ijest.v4i2.14
|View full text |Cite
|
Sign up to set email alerts
|

Bending analysis of laminated composite plates using finite element method

Abstract: Laminated composite plate structures find numerous applications in aerospace, military and automotive industries. The role of  transverse shear is very important in  composites, as the material is weak in shear due to its low shear modulus compared to extensional rigidity. Hence, an accurate understanding of their structural behaviour is required, such as deflections and stresses. In this paper, a number of finite element analyses have been carried out for various side-to-thickness ratios, aspect ratios and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 31 publications
0
27
0
2
Order By: Relevance
“…They attributed the paradox to the fact that the energy functional was not self-adjoint, as Reddy [33] first noticed. To overcome this paradox and satisfy the self-adjoint condition for the energy functional, Challamel et al suggested a transformation into the boundary conditions of the cantilever beam.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…They attributed the paradox to the fact that the energy functional was not self-adjoint, as Reddy [33] first noticed. To overcome this paradox and satisfy the self-adjoint condition for the energy functional, Challamel et al suggested a transformation into the boundary conditions of the cantilever beam.…”
Section: Introductionmentioning
confidence: 92%
“…At the same time, Reddy [33] researched into the nonlocal differential form by deducing the equations of motion and the corresponding boundary conditions through Hamilton's principle for a number of bending theories. What is more, Reddy reached the conclusion that it was not possible to formulate the underlying quadratic functionals for nonlocal differential beam theories.…”
Section: Introductionmentioning
confidence: 99%
“…However, such machines are costly and cannot be afforded by some countries and hence researchers developed a computer aided system (CAS) to fulfill such task. The CAS components are usually consists of four main modules which are preprocessing, segmentation, post processing and counting [4][5] [6]. In the modules, the most important components are WBC segmentation and counting.…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods used for counting purposes that consider a clumped regions. Some of the methods are distance transform [8], edge detection [9] and Circle Hough Transform (CHT) [5] [6]. Among this method, CHT is mentioned to perform better for estimating number of cell in the clumped regions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Paulo et al [10] carried a finite element analysis (FEA) to predict the complex mechanical behavior under heat affected zone of integrally stiffened panels when subjected to compressive loads, and particularly the ultimate load level, in the presence of elasto-plasticity, using ABAQUS for two types of stiffener such as trapezoidal and L-shaped. The result shows that the increase of the magnitude of the imperfections has a significant influence in the variation trend of the ultimate load levels, depending on the shape chosen for the imperfection.…”
Section: Figure 1: Aircraft Fuselage [2]mentioning
confidence: 99%